A case report of isotretinoin-induced manic psychosis - Jisha M Lucca; Niphy Annie Varghese; Madhan Ramesh; Dushad Ram (Wolters Kluwer Medknow Publications, 2016)
Isotretinoin, an oral vitamin A derivative, used to treat severe treatment-resistant acne. Psychiatric side effects of isotretinoin particularly depression and suicidal thoughts have been well documented. We report a case of isotretinoin-induced manic psychosis in a young female without a family history and history of mental illness.